1998
DOI: 10.1093/humrep/13.10.2869
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of day 3 embryo morphology regarding blastocyst formation, pregnancy and implantation rate after day 5 transfer following in-vitro fertilization or intracytoplasmic sperm injection

Abstract: The transfer of blastocysts has been associated with a very high implantation rate. However, not all embryos achieve the blastocyst stage. Our study was set up to demonstrate whether embryo morphology on day 3 predicts subsequent blastocyst formation. A prospective study was carried out in 48 patients with a mean of 2.9 failed in-vitro fertilization (IVF) attempts. In this new cycle, the morphology of the embryos on day 3 was noted. After pre-selection of the embryos which would have been transferred on day 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(101 citation statements)
references
References 13 publications
5
91
0
2
Order By: Relevance
“…However, selection based on morphology is highly controversial in literature, where some of them say that embryos with a compromised morphology still give viable pregnancies (28,41).…”
Section: Discussionmentioning
confidence: 99%
“…However, selection based on morphology is highly controversial in literature, where some of them say that embryos with a compromised morphology still give viable pregnancies (28,41).…”
Section: Discussionmentioning
confidence: 99%
“…These were higher than those reported in most blastocyst studies even though only 0.88, 0.80, and 0.61 more embryos were cultured for Groups I, II, and III, respectively, than the number transferred. Pregnancy and implantation rates with blastocyst transfer have ranged from 21 to 77% and 9-62%, respectively (2,5,6,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). With blastocyst transfer, all embryos are retained in culture to ensure at least two high-quality blastocysts are available for transfer.…”
Section: Discussionmentioning
confidence: 99%
“…With current cryopreservation techniques, human embryos survive and implant at higher rates when cryopreserved at the PN-S (8-10) compared with the cleavage or blastocyst stages (6,19,29,30). The cohort of fertilized oocytes from a retrieval cycle has better nuclear synchrony at the PN-S than do the embryos as they progress to later stages of development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rjinders and Jansen [23] also reported that only 51 % of the embryos transferred on day five had been selected for transfer on day three. Chen and Katerra [24] demonstrated that there is no difference, in terms of implantation and pregnancy, between whether PN morphology or early cleavage is used to select embryos for transfer on day three.…”
Section: Introductionmentioning
confidence: 99%